Lucans poetische Technik : Studien zum historischen Epos - Radicke, Jan. (Mnemosyne, Supplements, 2004)
The present volume on Lucan's poetical technique focusses on the main artistic principles of the Pharsalia, studying both the underlying history of the Civil War and its poetical reworking by the author. A chapter on Lucan's historical source (Livy) is followed by a chapter on Lucan's poetical technique and the general outline of his work. The material basis for these chapters is provided by a detailed analysis of every single book of the Pharsalia, which takes the form of a \'historical-poetical\' commentary. The study closes with a chapter on the narrator and the author.